Reading Paulo Freire’s Pedagogy of the Oppressed: Why did it feel empowering to me (Ensino, Saúde e Ambiente, 2021)
Celebrating the work of Paulo Freire for his healing influence, this paper gives an auto-ethnographic account of the author’s personal, pedagogical and political liberation process reading Paulo Freire’s Pedagogy of the Oppressed. Raised in a conservative patriarchal middle-class atmosphere in central Turkey, the author analyzes her own story of liberation as a woman, as a young scholar, as non-native English-speaking language educator and a citizen of a democratic republic. The author describes how she realized her own subjugation by reading Freire (2005) at a time of personal and political crisis and how she tried hard to find her personal voice. She also depicts the impact of the book on her pedagogy, on her relationships with students and on her liberatory praxis. Finally, the author tells how she transformed her understanding of the dynamics of social transformation reading Freire’s dialogic, problem-posing pedagogy of the oppressed.